Green marketing and its effect on consumers' purchase behaviour: an empirical analysis / Norsiah Ahmad ... [et al.] - Ahmad, Norsiah; Ghazali, Norfazlina; Abdullah, Mohamad Fariz; Nordin, Raslan; Mohd Nasir, Intan Najihah; Mohd Farid, Nur Amira (Universiti Teknologi MARA, 2020)
Over the years, environmental concerns have been extensively discussed. Natural resources are increasingly being diminished for the unscrupulous benefits of business profitability, resulting in an inherent need for alternative solutions. Following this, an application of green marketing concept could be warranted in pursuit of an augmented awareness on environmental conservations. This study aims to investigate the extent to which green marketing tools, namely, eco-brand, eco-labelling, ecopackaging and environmental advertisement affect consumers' purchase behaviour towards greenrelated products or services. Using a non-probability sampling technique, a total of 300 survey questionnaires were distributed to targeted respondents. However, only 189 feedbacks were usable for further statistical analyses. Regression result revealed that only eco-packaging and environmental advertisement had significant effects on consumer purchasing behaviour. Eco brand and eco labelling proved otherwise. Several managerial implications are further discussed.